PENGARUH PERSENTASE PENAMBAHAN SIKA VISCOCRETE-10 TERHADAP KUAT TEKAN BETON - Muhammad Zardi; Cut Rahmawati; T Khamarud Azman (Center for Research and Community Service (LPPM) University of Abulyatama, 2016)
Building structure often use concrete as the main structural material, in which the concrete-forming materials such as cement, sand, gravel, water and additives. The aim of study is to investigate the influence of addition of Sika Viscocrete-10 toward concrete compressive strength. Concrete is planned with Water Cement Ratio 0.3. Slump values obtained for normal concrete with maximum aggregate diameter of 25.4 mm is 7.8 cm. The values are in accordance with the slump plan of 7.5 to 10 cm, meanwhile values slump that use Sika Viscocrete-10 as much as 0.5% is 19.5 cm; Sika Viscocrete-10 as much as 1% is 21.9 cm; Sika Viscocrete-10 as much as 1.5% is 23 cm; and Sika Viscocrete-10 as much as 1.8% is 24.7 cm. Based on these test results, the conclusion is addition of Sika Viscocrete-10 is able to enhance the workability value of concrete, so it is easy to work. Concrete mix design using the American Concrete Institute (ACI). Specimens used in this study is a standard concrete cylinder diameter of 150 mm and a height of 300 m, tested after the age of 14 days. Number of test specimens for all treatments is 25 with 5 specimens in each treatment. The average compressive strength of concrete with normal mixture is 295.43 kg/cm2; for concrete with Sika Viscocrete-10 as mush as 0.5% is of 376.50 kg/cm2; Sika Viscocrete-10 as mush as 1% is 452.94 kg/cm2; Sika Viscocrete-10 as mush as 1.5% is 501.63 kg/cm;2 and Sika Viscocrete-10 as mush as 1.8% is 515.78 kg/cm2. Concrete compressive strength greater with increasing percentage of Sika Viscocrete-10.